Interception Studies in Sal (Shorea robusta) Coppice forest - Ghosh, R. C.; Subba Rao, B. K.; Ramola, B. C. (Indian Forester, 1980)
This paper presents the results of interception studies carried out during 1977 in coppice sal forest at Rajput Forest Experiment Station, (Rajpur Forest Block, West Dehra Dun Division) to evaluate the effect of thinning on the interception loss. This study is one of a series of hydrological studies that are being carried out at Forest Research Institute, Dehra Dun. It is proposed develop mathematical models by using the results of these studies, to predict hydrological behaviour of forested watersheds. These models also enable us to predict the effect of management operations and biotic influences on the hydrological behaviour. Present study has shown that the interception loss decreases with increasing amount of rainfall and that a reduction of crown density by 22% has resulted in a reduction of interception by 5% in coppice sal forest. Also, it has been observed that interception loss depends upon rainfall and vegetation characteristics.